Bone marrow granulomatosis: two case reports - Giacomo Andreani; Alessandro Morotti; Matteo Dragani; Francesca Caciolli; Bruna Crea; Valerio Marci; Ubaldo Familiari; Angelo Guerrasio (Italian Journal of Medicine, 2019)
Bone marrow granulomatosis is not a common finding and remains a diagnostic challenge. Here below we report two bizarre but not so rare cases of bone marrow granulomatosis: bone marrow involvement by M. avium-intracellulare and reaction to intravesical administration of bacille of Calmette-Guèrin for non-muscle-invasive bladder cancer; two distinct culprits suggesting the wide range of possible causative factors of this histopathological pattern. In the discussion we provide a brief overview of causes and suggestions for a diagnostic approach.